2020
DOI: 10.1093/europace/euaa005
|View full text |Cite
|
Sign up to set email alerts
|

Prediction models for atrial fibrillation applicable in the community: a systematic review and meta-analysis

Abstract: Aims Atrial fibrillation (AF) is a common arrhythmia associated with an increased stroke risk. The use of multivariable prediction models could result in more efficient primary AF screening by selecting at-risk individuals. We aimed to determine which model may be best suitable for increasing efficiency of future primary AF screening efforts. Methods and results We performed a systematic review on multivariable models derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 63 publications
3
51
1
Order By: Relevance
“…Our study indicates that a CHA 2 DS 2 VASc > 0 in males and >1 in females, or its analogue CHA 2 DS 2 VA > 0, can be useful risk stratifiers for detecting unknown AF, since associated with very high sensitivity for AF detection in the whole population. Our study found that female sex is negatively associated with AF detection at screening, a finding not stressed in previous meta-analyses [ 13 , 15 ], but considered in some scores used for predicting incident AF in the community [ 32 ]. The direct implications of this observation is the opportunity to modify CHA 2 DS 2 VASc, for the purpose of AF screening, into a sex neutral score (CHA 2 DS 2 VASc > 0 in males and >1 in females) or a sex-independent score CHA 2 DS 2 VA > 0).…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Our study indicates that a CHA 2 DS 2 VASc > 0 in males and >1 in females, or its analogue CHA 2 DS 2 VA > 0, can be useful risk stratifiers for detecting unknown AF, since associated with very high sensitivity for AF detection in the whole population. Our study found that female sex is negatively associated with AF detection at screening, a finding not stressed in previous meta-analyses [ 13 , 15 ], but considered in some scores used for predicting incident AF in the community [ 32 ]. The direct implications of this observation is the opportunity to modify CHA 2 DS 2 VASc, for the purpose of AF screening, into a sex neutral score (CHA 2 DS 2 VASc > 0 in males and >1 in females) or a sex-independent score CHA 2 DS 2 VA > 0).…”
Section: Discussionmentioning
confidence: 47%
“…The lack of benefit found in this study in active screening arm can be explained by the high rate of AF detection that characterizes usual care in The Netherlands, as a result of implemented guidelines for cardiovascular disease management, resulting in a higher baseline prevalence of AF as compared with the SAFE study [ 31 ]. To reduce the complexity of screening initiatives, a series of studies evaluated the possibility of an improved patient targeting, by the selection of candidates with a higher likelihood to have AF detected [ 32 ]. The CHA 2 DS 2 VASc score, even if not developed for this purpose, has been tested in the form of “virtual” CHA 2 DS 2 VASc, both for screen-detected and incident AF [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been validated in various community cohorts 5–10 and appears to be the most viable prediction model for patient selection in future community AF screening. 11 …”
Section: Introductionmentioning
confidence: 99%
“…In the general population, prior studies have proposed several risk models that specifically been derived for predicting incident AF such as the Framingham risk score, the Atherosclerosis Risk In Communities Study (ARIC) score, CHADS2, CHA2DS2-VASc, and CHARGE-AF (Cohorts for Heart and Aging Research in Genomic Epidemiology). 23 A systematic review by Himmelreich et al 23 has summarized all of these 10 risk models (Supporting Information, Figure S3), suggesting that the CHARGE-AF score seems to be the most suitable tool for screening AF in the community. In addition, Himmelreich et al 23 also found that the CHADS2 and CHA2DS2-VASc scores have also been used to predict incident AF in the general population, where the pooled C-indexes for the CHADS2 and CHA2DS2-VASc scores were 0.66 (95% CI: 0.59-0.74), and 0.69 (95% CI: 0.64-0.74), respectively.…”
Section: Comparisons With Previous Studiesmentioning
confidence: 99%